Estudo etnobotânico, microbiológico e perfil toxicológico in vitro e in vivo de Rhaphiodon echinus (Nees & Mart) Schauer - Duarte, Antônia Eliene (2016)
Medicinal plants have long been used in traditional medicine for the treatment of various diseases, especially because they have low cost and lower toxicity compared to synthetic drugs. The pharmaco-toxicological interest of these products have generated considerable interest to the scientific community. In this context, species of Lamiaceae family deserve particular importance not only because of their applicability in food industry and cosmetics, but also due to their ethnopharmacological use. The species Rhaphiodon echinus (Nees and Mart) Schauer, popularly known as “betônica”, is distributed in Northeastern part of Brazil and infusions of its leaves are used as a tea for the treatment of inflammation, microbial infection and as antitussive agent. In spite of its use, there is however no report on the toxicity of this plant. In addition, there is no scientific evidence that can support the therapeutic use of R. echinus in Brazilian folk medicine. Thus, the objective of this study was to investigate the ethnobotanical and toxicological profile of R. echinus in different experimental models, as well as to evaluate its phytochemical profile and antioxidant potential in in vitro models. Particularly, we evaluated the toxicity profile of the infusion of the leaf extracts of R. echinus (AEREi) in different species (Artemia salina, Rhamdia quelen, Rattus norvegicus) and the potential antioxidant and cytotoxic activity of aqueous (EARE) and ethanolic (EERE) extracts of the leaves of R. echinus. In addition, R. echinus leaf essential oil was investigated alone or in combination with anti-fungal (fluconazole and nystatin) and antibiotics (gentamycin, amikacin, ciprofloxacin and imipenem) against various bacteria (Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa) and fungal (Candida albicans, Candida krusei and Candida tropicalis) strains. Furthermore, the chemical composition of R. echinus leaf essential oil and the extracts (infusion (EAREi), EARE, EERE) was performed using CG-MS and HPLC respectively. The results indicated that the extracts (infusion (EAREi), EARE, EERE) contain gallic, chlorogenic, caffeic and ellagic acids, quercetin and rutin. The estimated IC50 at 24 h and 48 h was 181.70 μg/mL (124.62-264.93) and 100.63 μg/mL (71.01-142.59), respectively with Artemia salina (confidence interval of 95%). However, the exposition of Rhamdia quelen to different concentrations of EAREi (1000-5000 mg/mL) was not associated with any mortality, indicating the absence of pro-oxidant activity. This was consistent with no change in reactive species (RS) generation and lipid peroxidation (LP) in the gills, kidneys, liver and brain in comparison to their respective control. The plasma levels of alanine aminotransferase (ALT), alanine aminotransferase (ALT) and gamma glutamyl transferase (GGT), indicated that various concentrations of EAREi were not hepatotoxic to Rhamdia quelen. In the second part of this study, the aqueous (EARE) and ethanolic (EERE) extracts of R. echinus displayed antioxidant activity by eliminating DPPH radicals IC50 = 111.9 μg/mL (EERE) and IC50 = 227.9 μg/mL (EARE). Both extracts inhibited the formation of thiobarbituric acid reactive substances (TBARS), induced by Fe2+ (10 μM) in rat brain and liver homogenates. EARE and EERE (30-480 μg/mL) did not induce genotoxicity, cytotoxicity or osmotic fragility on human blood cells. The results obtained by the microdilution method revealed low antifungal and antibacterial activity of R. echinus leaf essential oil with MIC ≥ 1 024 μg/mL). However, it was able to modulate the activity of the antimicrobial agents tested, when added to the growth medium at the sub-inhibitory concentration (i.e., MIC/8 = 128 μg/mL). R. echinus leaf essential oil showed the potential to chelate Fe(II), indicating that it may be of therapeutic importance for the treatment of neurodegenerative and infectious diseases. The essential oil revealed the presence of monoterpenes and sesquiterpenes, which can be at least partly responsible for the modulatory action of the oil, being a natural product capable of enhancing the antibacterial and antifungal activity of antimicrobial drugs. However, the results suggest that R. echinus can prevent / protect against diseases associated with oxidative damage, and indicate that the essential oil of the leaves can modulate the antibacterial and antifungal activity of antimicrobial drugs.